ANALISIS QOS VIDEO STREAMING JARINGAN WIRELESS (STUDI KASUS: TAMAN INTERNET ENGKU PUTRI BATAM) - Nopriadi, Nopriadi; Arnomo, Sasa Ani (Computer Based Information System Journal, 2020)
The increasing number of internet users in Indonesia has an impact on increasing the number of users of streaming video. The increase in the number of users is based on technological developments with the emergence of mobile devices such as notebooks, tablets and smartphones equipped with internet access via wireless networks. Unlike networks using cables, the characteristics of using video streaming over wireless networks are limited when compared to those using cables. To access various applications on the internet, including video streaming, a stable internet service is needed. For this reason, a Quality of Service (QoS) measurement research is needed which is carried out at one of the wireless network provider points in the city of Batam, namely Taman Internet Engku Putri. QoS can be used to measure and analyze the stability and quality of a wireless network. The parameters used in the measurement and analysis of QoS are Throughput, Delay, Jitter and Pakect Loss which will be tested on video streaming services. The test will be carried out at certain times such as peak hours and low hours. Low hours usually range from 08.00 WIB - 15.00 WIB and rush hour usually ranges from 15.00 WIB - 21.00 WIB. The results of measurement and analysis using four QoS parameters show that the video streaming service using wireless networks in Taman Internet Engku Putri is in the medium category.